Precalculus help!!
1. Find the derivative of f(x) = 6 divided by x at x = -2.
and
2. Find the derivative of f(x) = 4x + 7 at x = 5.
Thank you. Need help solving, will medal.

- anonymous

- jamiebookeater

See more answers at brainly.com

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga.
Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus.
Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this

and **thousands** of other questions

- freckles

I bet you are practicing using the formal definition and not the short cuts right?

- anonymous

Yes @freckles

- freckles

you could use either one of these:
\[f'(a)=\lim_{h \rightarrow 0}\frac{f(a+h)-f(a)}{h} \text{ or } f'(a)=\lim_{x \rightarrow a} \frac{f(x)-f(a)}{x-a}\]

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

- freckles

they are the same definition just written a little different

- freckles

which one are you more comfortable with?

- anonymous

I'm not sure, I'm still confused with both.

- freckles

Ok we could do question one together both ways
and you can decide which way you want to use for the second and I will check your work for that one

- anonymous

Ok thanks!

- freckles

\[a=-2 \\ f(x)=\frac{6}{x} \\ f(a)=f(-2)=\frac{6}{-2}=-3 \\ f(a+h)=f(-2+h)=\frac{6}{-2+h}\]
first do you understand how I got f(a+h) and f(a) for the first one?

- anonymous

Yes completely.

- freckles

Ok I'm going to input them into the formula

- freckles

\[f'(a)=f'(-2)=\lim_{h \rightarrow 0}\frac{\frac{6}{-2+h}-(-3)}{h}\]

- freckles

\[f'(-2)=\lim_{h \rightarrow 0}\frac{\frac{6}{-2+h}+3}{h}\]

- freckles

ok the trick is to get that h on the bottom to cancel somehow so we can actually plug in h=0

- freckles

notice we have a compound fraction

- freckles

that is a fraction inside a bigger fraction

- anonymous

Hold on super quick, writing this down.

- anonymous

Ok got it.

- freckles

we want to see if we can "simplify" the fraction
that means get rid of the compound fraction
notice the little fraction has denominator (-2+h)
multiply top and bottom by (-2+h)
this will make our compound fraction into a "simple" fraction
do you want to try multiplying top and bottom by (-2+h)

- freckles

and let me know what the result is just doing that one step

- anonymous

Yes

- anonymous

Do I multiply the top and bottom of just the little fraction?

- freckles

multiply top and bottom by (-2+h) of the big fraction

- anonymous

Would it be 9/h(-2+h) ?

- freckles

that isn't a bad try ... I think the 9 is just a bit off...should be 3 there
\[\lim_{h \rightarrow 0} \frac{\frac{6}{-2+h}+3}{h} \cdot \frac{-2+h}{-2+h}=?\]
\[\lim_{h \rightarrow 0} \frac{\frac{6(-2+h)}{-2+h}+3(-2+h)}{h(-2+h)} \\ =\lim_{h \rightarrow 0}\frac{6+3(-2+h)}{h(-2+h)}\]

- freckles

3(-2+h)=-6+3h

- freckles

\[\lim_{h \rightarrow 0} \frac{6-6+3h}{h(-2+h)}\]

- anonymous

Oh ok, I see. So it would be 3h/h(-2+h)?

- freckles

\[\lim_{h \rightarrow 0}\frac{3h}{h(-2+h)}\]
you should recall h/h=1 (we can say this since h is not 0)

- freckles

\[\lim_{h \rightarrow 0}\frac{3 \cancel{h}}{\cancel{h}(-2+h)}\]

- freckles

guess what ?

- anonymous

So then we are left with 3/-2+h

- freckles

we are going to have no problems pluggin in 0 for h now
because this function 3/(-2+h) actually exists at h=0

- freckles

so what do you think f'(-2)=?

- anonymous

But how do you know that the function exists at 0?

- freckles

because the bottom is not 0 when h is 0

- anonymous

Oh ok got it, so would f'(-2) = 3/-2?

- freckles

yes

- freckles

or -3/2

- freckles

doesn't matter where you put the negative at

- anonymous

Could you check my other question once I solve it?

- freckles

k..
while you are working it
I'm going to do the first one again but use the other formula I wrote

- anonymous

Ok (:

- anonymous

Is the second one f(5) = 4?

- freckles

\[f'(a)=\lim_{x \rightarrow a}\frac{f(x)-f(a)}{x-a} \\ a=-2 \\ f(x)=\frac{6}{x} \\ f(a)=f(-2)=\frac{6}{-2}=-3 \\ f'(a)=f'(-2)=\lim_{x \rightarrow -2} \frac{\frac{6}{x}+3}{x+2} \\ \text{ multiply \top and bottom by } x \\ f'(-2)=\lim_{x \rightarrow -2} \frac{6+3(x)}{(x+2)(x)} \\ f'(-2)=\lim_{x \rightarrow a}\frac{3(x+2)}{(x+2)(x)} \\ \text{ notice} \frac{x+2}{x+2}=1 \text{ for when } x \neq -2 \\ f'(-2)=\lim_{x \rightarrow -2} \frac{3}{x} =\frac{3}{-2} \text{ or } \frac{-3}{2} \text{ or } -\frac{3}{2} \text{ or } -1.5\]

- freckles

oops one sec let me check

- freckles

"2. Find the derivative of f(x) = 4x + 7 at x = 5."
f(5)=4(5)+7=20+7=27

- anonymous

Oh ok, I'm used to the first version we used though. But the one you just used also makes a lot of sense. (:

- anonymous

Yes, and for f(a+h) I got it = to 27+h

- freckles

did you mean f'(5)=4?

- anonymous

Yes that's what I meant.

- freckles

that is right

- anonymous

Could you check this one too?
The position of an object at time t is given by s(t) = -8 - 9t. Find the instantaneous velocity at t = 1 by finding the derivative.

- freckles

yeah this question is basically the same as the last questions you asked
just asked it in word problem form

- anonymous

Would it be:
f'(1) = 9?

- freckles

the velocity=derivative of position
v(t)=s'(t)
They are using to find s'(1)

- freckles

close

- freckles

not exactly though

- freckles

you are missing a sign

- freckles

\[v(1)=s'(1)=\lim_{h \rightarrow 0}\frac{s(1+h)-s(1)}{h}\]

- anonymous

-9?

- freckles

yes

- anonymous

My bad, didn't catch the negative sign.

- freckles

are you using short cuts?
or the long way?

- freckles

because you found that really fast

- anonymous

The long way but using mental math

- freckles

nice

- anonymous

I have the steps written down though, the long way. Would this be ok for an answer:
First, I used:
s(t) = -8 - 9t and t=1 to solve for (a+h) and (a). My 'a' term would be 1 in this case.
f(a) = -8 - 9t = -8 - 9(1) = -17
f(a+h) = -8 - 9t = -8 - 9(1+h) = -17 - 9h
Then I used the equation:
f'(a) = lim[f(a+h) - f(a)/h] = f'(a) = -17 - 9h - (-17)/h = -9h/h = -9
Thus I found the derivative to be:
f'(1) = -9

- freckles

s(t) = -8 - 9t
notice the slope of s(t) is -9
the derivative of s(t) is -9

- freckles

but yeah your teacher probably wants you to use that formal definition of derivative thing
but you know we remember from algebra that the slope of f(x)=mx+b is m
and we learn from calculus that the slope is the derivative

- anonymous

Ok, but is the way I showed my work using the formal definition?

- freckles

yes it is pretty too

- freckles

you did very well

- freckles

only thing I would say
and it is really not apart of your work
"s(t) = -8 - 9t and t=1 to solve for (a+h) and (a). My 'a' term would be 1 in this case.
:"
I would say f(a+h) and f(a)
but I knew what you meant when you said this

- freckles

oops s(a+h) and s(a)
since our function name is s not f

- freckles

you could change all those f letters to s letters actually

- anonymous

Ok thanks!

- freckles

np

- anonymous

Thanks for all your help!!

- anonymous

I will be doing another test similar if you could help me later on? @freckles Maybe in an hour or so.

Looking for something else?

Not the answer you are looking for? Search for more explanations.